More animal per drop: searching for livestock– water productivity gains in the Nile Basin - Peden, Donald G. (CGIAR Challenge Program on Water and Food, 2008)
Good management of livestock watering is critical to maintaining the quality of the environment and human health. The use of troughs or other dedicated water points that are separate from human water sources can prevent contamination by waterborne diseases. It also conserves riparian vegetation and leaves stream and river sediments undisturbed. Provision of water to dairy cattle in their stalls greatly reduces the stress on them, allowing significant increases in milk production.